Microsponge Delivery System: Revolutionizing Drug Delivery in Pharmaceutical Research - Ranu Biswas; Md. Ahesan Ansari; Sourav Mondal; Pritam Kapat; Arindam Ghosh; Shounak Sarkhel (Pharmaceutical Research - Recent Advances and Trends Vol. 4, 2024)
Microsponge is a porous polymeric microsphere and a tiny sponge-like spherical particle. It is a novel, unique and futuristic approach to drug delivery in a well-framed manner. Using this approach, regulated delivery of drugs may now be gained quickly as well as safely. This system is a patented system of tiny particles, made up of very tightly connected, polymer-based microporous spheres filled with active ingredients, each containing many small, interconnected empty spaces. Sponge micro particulates have gained the interest of researchers for pharmaceutical applications due to their exceptional features, which include high porousness, elastic deformation, capillary action, and three-dimensional (3D) response surroundings. Sponge particles are particularly promising for medication administration, tissue engineering, and wound repair due to their large reservoirs with extensive surfaces and interior networks for cargo sheltering and shuttling. Topical drug delivery is the exclusive application of microsponge but later on, the other application routes of drug delivery like oral, pulmonary and parenteral were also used. One of the most excellent features of the microsponge is it is self-sterilizing. The release and loading of drugs were studied by researchers and indicated the properties responsible for them. This review focused on the incorporation of drugs in microsponges, fabrication methods, characterization parameters, and biomedical applications of microsponges. Near future, it will be quite useful in exploring the microsponge delivery systems (MDS) in different disorders. So, the objective of this work was to provide recent and updated information on Microsponges as smart carriers for drug delivery in Pharmaceutical research.